A nonsense mutation of human XRCC4 is associated with adult‐onset progressive encephalocardiomyopathy - Leonardo Bee; Alessia Nasca; Alice Zanolini; Filippo Cendron; Pio d'Adamo; Rodolfo Costa; Costanza Lamperti; Lucia Celotti; Daniele Ghezzi; Massimo Zeviani (EMBO Molecular Medicine)
Abstract We studied two monozygotic twins, born to first cousins, affected by a multisystem disease. At birth, they both presented with bilateral cryptorchidism and malformations. Since early adulthood, they developed a slowly progressive neurological syndrome, with cerebellar and pyramidal signs, cognitive impairment, and depression. Dilating cardiomyopathy is also present in both. By whole‐exome sequencing, we found a homozygous nucleotide change in XRCC4 (c.673C>T), predicted to introduce a premature stop codon (p.R225*). XRCC4 transcript levels were profoundly reduced, and the protein was undetectable in patients' skin fibroblasts. XRCC4 plays an important role in non‐homologous end joining of DNA double‐strand breaks (DSB), a system that is involved in repairing DNA damage from, for example, ionizing radiations. Gamma‐irradiated mutant cells demonstrated reduction, but not abolition, of DSB repair. In contrast with embryonic lethality of the Xrcc4 KO mouse, nonsense mutations in human XRCC4 have recently been associated with primordial dwarfism and, in our cases, with adult‐onset neurological impairment, suggesting an important role for DNA repair in the brain. Surprisingly, neither immunodeficiency nor predisposition to malignancy was reported in these patients.